COVID-19 Impact Monitoring at the Household Level : Burkina Faso, Brief No. 6 - Tsimpo Nkengne, Clarence; Tiberti, Marco; Backiny-Yetna, Prospere R.; Costantini, Marco; Koncobo, Zakaria; Tiendrebeogo, Adama (World Bank, Washington, DC, 2021)
This note presents the results of the sixth round of a nationally representative telephone survey (HFPS). The BFA Covid -19 HFPS - Round 6 was administered between January 15 and February 01, 2021. The following modules were administered during the 6th round: Access to basic services; Employment and income; Agriculture; Food Safety; Shocks; and Conflicts. In addition to the 1,944 households interviewed successfully in the fifth wave, in order to maintain the sample size, 84 other households which had not been interviewed successfully in the previous rounds but who had not refused to participate in the survey . the investigation w ere called during this sixth wave. 24 households were excluded from the sample for the sixth wave because they refused to participate in the fifth wave. 2008 households (96.96 percent of 2,071 attempts) were contacted and 1,985 (95.85 percent) were successfully interview ed. Among those contacted, 18 households categorically refused to be interviewed. For the sake of simplicity, this note focuses on modules related to food security, agricultural income, shocks, and conflicts.